PENGARUH PRICE DISCOUNT DAN BONUS PACK TERHADAP IMPULSE BUYING (STUDI KASUS PADA PELANGGAN ALFAMART DI KOTA JAMBI) - Ade Wahyu Ramadhan; Novita Ekasari (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study aims to determine: (1) the effect of price discount on impulse buying on Alfamart customers (2) the effect of bonus packs on impulse buying on Alfamart customers (3) the most dominant influence on impulse buying on Alfamart customers. This research was conducted on all Alfamart customers in the city of Jambi. This research includes relationship research using a quantitative approach. The population in this study were all Alfamart customers in Jambi City. The sampling technique used purposive sampling method with a total sample of 100 people. The data collection technique uses an online questionnaire that has been tested for validity and reliability, and the data analysis technique used is multiple regression. The results showed that (1) there was a positive effect of price discount on impulse buying for Alfamart customers, as evidenced by the t-count value of 2.087, significance of 0.04 <0.05 and the regression coefficient having a positive value of 0.250; (2) there is a positive effect of bonus packs on impulse buying for Alfamart customers, as evidenced by the t-count value of 3.556, a significance of 0.001 <0.05 and the regression coefficient has a positive value of 0.426; (3) the bonus pack has the most dominant effect on impulse buying with a regression coefficient value of 0.426, which is greater than the price discount regression coefficient of 0.250. Key words : Price Discount, Bonus Pack, Impulse Buying.